Photojournalism in the Belém Press: 1900–1950 - Seixas, Netília Silva dos Anjos; Siqueira, Thaís Christina Coelho (Brazilian journalism research, 2015)
This study looks at the course of photojournalism in the first half of the 20th century in the Belém press, in the State of Pará. This is exploratory research based on the iconographic and iconological analysis of images as understood by Panofsky and Kossoy. Bibliographical and documentary research together with an empirical analysis of data was conducted on three important newspapers in Pará: A Província do Pará, Folha do Norte and Estado do Pará, all available in the archives of the Arthur Vianna Public Library in Belém. Analyzing the data made it possible to provide a picture of the course of photojournalism in Pará for the major newspapers in circulation during the established time period, showing that even at the beginning of the century periodicals already recognized the power of images; something evident in publication. The data also showed that problems in the city, wars, politics, police and sports were the main issues for photojournalism in Pará throughout the decades studied in this paper.